The Improvement on the Visual Painting Inspection Process Flow of Train for Kuala Lumpur Additional Vehicle (KLAV) 27 Project - Umi Umaira binti Shaari,; Karthigesu A/L Nagarajoo,; Mohd Noor Fathullah Mohd Noordin,; Muhammad Zulhilmy Yaman, (Progress in Engineering Application and Technology, 2023)
The project is based on an ongoing Bombardier-Hartasuma Consortium Project, which is Kuala Lumpur Additional Vehicle (KLAV) 27. The problem that occurred in the project is the delay in train delivery to the client that is due to the multiple detail inspection stages and the facility could not provide enough lighting. The project aims to prevent project delay and extended work by improving the inspection process flow for train production by analyzing standard acceptance criteria and providing guidelines for visual, safety, and functional inspectional will help shorten the process and reduce time-consuming inspection. Implementing the Rig Platform also will shorten the inspection flow, ensuring no delays and extended work due to multiple stages.